The Development of Tolerance Through Islamic Education Among Islamic Minorities in Hindu-Majority Communities - Muhammad Fazlurrahman Hadi; Usbani (Universitas Muhammadiyah Malang, 2024)
This research is encouraged by the many conflicts in a society represented by the majority-minority and religion, leading to acts of violence, moral crises, and anarchism. Therefore, many parties then developed the role of education, especially Islamic education, amid non-Muslim communities. So, it is essential to analyze the behavior of the Muslim minority amid the Balinese Hindu majority community. How is the content and provision of the values of tolerance at the Bali Bina Insani Islamic Boarding School as a model of religious moderation? The purpose of this research is to analyze, test, and describe the life of a Hindu-majority society that is moderate towards Muslim minorities and, conversely, the development of Islamic values in the form of tolerance at the Bali Bina Insani Islamic Boarding School towards minority Hindu teachers and employees in it. This research shows that despite a Muslim minority in an Islamic boarding school entity amidst a Hindu majority, there are no acts of intolerance. And vice versa, even though there are teachers and employees at the Islamic boarding school who are Hindus (as a minority), they are still given rights that are by work professionalism, and there is no discrimination against them.